Interdisciplinary perspectives on business convergence, computing, and legality - Khurana, Reema, 1968-; Aggarwal, Rashmi; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book investigates the development of convergent and interoperable systems in business environments, with a particular focus on potential legal implications that emerge when a company begins branching out into domains traditionally occupied by suppliers and consumers"--Provided by publisher.
Knowledge sharing centric competitive business intelligence to guide convergence / Mei-Tai Chu -- Comparative analysis of selected websites of brokerage houses in Poland / Witold Chmielarz -- Factors influencing tourists' motivational determinants for promotion of tourism destination: an empirical assessment on rural tourism with special reference from Kamarpukur, West Bengal / Nilanjan Ray -- Analysis of facts for companies going public through social media / Dilip Kumar Mallick, Susmi Routray -- Emerging legal trends on hyperlinks and meta-tags: a discourse / Ameen Jauhar -- Compliance and regulatory standards for cloud computing / Jitendra Singh, Vikas Kumar -- Business to rural: the future of IT outsourcing / Kallol Sarkar -- Analysis of the outsourcing models and recommendation: case of outworks / Benu Sagar Dubey, Gopakumar K, Mukesh Singh -- Aspects of client vendor relationship and the risks therein / Daisy Mathur Jain -- Impact of managerial atmosphere on turnover intent in the private education institutions of West Bengal / Soumen Chatterjee, Paramita Sarkar -- Factors influencing the effectiveness of C2C websites in Delhi-NCR / Teena Bagga, Roushan Chouhan -- Secure multiparty computing protocol: a secure approach in multiparty computation / Zulfa Shaikh, Poonam Garg -- Making a case for information integrity in healthcare / Reema Khurana, Vijay V. Mandke -- Modeling complex errors for information integrity analysis / Reema Khurana, Vijay V. Mandke -- Dispute settlement for cyber crimes in India: an analysis / Rashmi Aggarwal -- Comparative analysis of major issues involved in IPR and competition policy / Nisha Dhanraj, Mamta Sharma -- Effects of phishing on e-commerce with special reference to India / Amita Verma -- An Indian legal perspective to protection of domain name: an analysis / Rashmi Aggarwal, Rajinder Kaur -- Data protection: a need of the hour for information technology enabled services (ITES) / Rajinder Kaur, Prabal Mehrotra -- Right to internet / Amita Verma, Amit Verma.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed July 16, 2013).
Keywords: Information technology -- Management; Internet marketing -- Social aspects; Electronic commerce -- Social aspects; Technological innovations -- Management; Convergence (Economics); Cyber crime; Data protection; E-commerce; Information security; Knowledge sharing; Legal trends; Regulatory standards; Social media; Software outsourcing models; Trademarks, copyrights, and domain names; Electronic books